Evolution of extreme waves and resonances - Galiev, Shamilʹ Usmanovich (Boca Raton, FL : CRC Press, 2020)
The theory of waves is generalized on cases of strongly nonlinear waves, multivalued waves, and particle-waves. The appearance of these waves in various continuous media and physical fields is explained by resonances and nonlinearity effects. Extreme waves emerging in different artificial and natural systems from atom scale to the Universe are explored. Vast amounts of experimental data and comparisons of them with the results of the developed theory are presented. The book was written for graduate students as well as for researchers and engineers in the fields of geophysics, nonlinear wave studies, cosmology, physical oceanography, and ocean and coastal engineering. It is designed as a professional reference for those working in the wave analysis and modeling fields.
OCLC-licensed vendor bibliographic record.
Keywords: Waves; Resonance; SCIENCE / Physics; TECHNOLOGY / Engineering / Mechanical